Ductile iron with composite layer and preparation method and application thereof

By forming a composite layer of silicate modified alumina and titanate modified zirconia on the surface of the ductile iron, combined with chromium oxide, the problem of poor corrosion resistance of ductile iron is solved, and its corrosion resistance and overall performance are significantly improved .

CN116240448BActive Publication Date: 2024-12-17HUNAN ZHANGHONG CASTING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211678218.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-26
Publication Date
2024-12-17
Estimated Expiration
2042-12-26

AI Technical Summary

Technical Problem

Ductile cast iron has poor corrosion resistance, which limits its application range.

Method used

Silicate modified alumina and titanate modified zirconia are used as the main components of the composite layer. The mixed oxide layer is formed by sintering to increase the density, and chromium oxide is added to reduce the sintering temperature and enhance the corrosion resistance of the composite layer. performance.

Benefits of technology

The corrosion resistance of ductile iron is significantly improved, and the overall performance of the composite layer is enhanced by increasing the density of the oxide layer and reducing the sintering temperature of chromium oxide.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a ductile iron with a composite layer and a preparation method and application thereof, belonging to the technical field of ductile iron; the cast iron includes ductile iron, and a composite layer is arranged on the surface of the ductile iron; the composite layer includes the following raw materials in weight fraction: 50% to 60% of silicate-modified aluminum oxide, 20% to 30% of titanate-modified zirconium oxide, and 3% to 5% of chromium oxide. In the invention, silicate-modified aluminum oxide and titanate-modified zirconium oxide are converted into oxides after sintering, thereby forming a composite layer composed of mixed oxides; during the sintering process, the oxides are filled with each other, thereby improving the density between the composite layers, thereby improving the corrosion resistance of the composite layers; at the same time, the chromium oxide can also reduce the sintering temperature, which is beneficial to improving the performance of the composite layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ductile iron production, and in particular relates to ductile iron with a composite layer and a preparation method and application thereof. Background Art

[0002] Ductile iron is a high-strength cast iron material with comprehensive properties close to those of steel. Based on its excellent properties, it has been successfully used to cast some parts with complex forces and high requirements for strength, toughness and wear resistance. Ductile iron has rapidly developed into a widely used cast iron material second only to gray cast iron. The so-called "iron instead of steel" mainly refers to ductile iron.

[0003] Ductile iron is made of spheroidized graphite through spheroidization and inoculation, which effectively improves the mechanical properties of cast iron, especially the plasticity and toughness, thus obtaining a higher strength than carbon steel. The chemical composition of ductile iron, except for iron, is usually: 3.0-4.0% carbon, 1.8-3.2% silicon, no more than 3.0% manganese, phosphorus and sulfur, and appropriate rare earth, magnesium and other spheroidizing elements.

[0004] Ductile iron needs to have good corrosion resistance during its application, but the corrosion resistance of ductile iron in related technologies is poor, which limits its application.

[0005] Therefore, the present invention provides a ductile iron having a composite layer, which has excellent corrosion resistance. Summary of the invention

[0006] An object of the present invention is to provide a ductile iron with a composite layer to solve at least one aspect of the problems and defects mentioned in the above background technology.

[0007] The invention also provides a method for preparing the ductile iron with the composite layer.

[0008] The invention also provides application of the ductile iron with the composite layer.

[0009] A first aspect of the present invention provides a ductile iron having a composite layer, comprising ductile iron,

[0010] The surface of the ductile iron is provided with a composite layer;

[0011] The composite layer includes the following raw materials in weight fractions:

[0012] Silicate-modified alumina 50% to 60%, titanate-modified zirconium oxide 20% to 30%, chromium oxide 3% to 5%.

[0013] According to one technical solution of the ductile iron technical solution with a composite layer of the present invention, at least the following beneficial effects are achieved:

[0014] Silicate-modified alumina and titanate-modified zirconia will be converted into oxides after sintering, thus forming a composite layer composed of mixed oxides; during the sintering process, the oxides will fill each other, thereby increasing the density between the composite layers, thereby improving the corrosion resistance of the composite layer; at the same time, chromium oxide can also reduce the sintering temperature, which is beneficial to improving the performance of the composite layer.

[0015] According to some embodiments of the present invention, the silicate-modified alumina comprises the following preparation raw materials:

[0016] Silicates and alumina.

[0017] According to some embodiments of the present invention, the silicate-modified alumina comprises the following preparation raw materials in parts by weight:

[0018] 0.1 to 0.2 parts of silicate and 1 part of aluminum oxide.

[0019] According to some embodiments of the present invention, the particle size of the aluminum oxide is 50 nm to 150 nm.

[0020] According to some embodiments of the present invention, the particle size of the aluminum oxide is 100 nm.

[0021] According to some embodiments of the present invention, the aluminum oxide is α-Al 2 O 3 .

[0022] According to some embodiments of the invention, the silicate is tetraethyl orthosilicate.

[0023] According to some embodiments of the present invention, the method for preparing the silicate-modified alumina comprises the following preparation steps:

[0024] After mixing aluminum oxide and water, an aluminum oxide dispersion is prepared;

[0025] Then, silicate and alkaline compound are added to the alumina dispersion to react.

[0026] According to some embodiments of the present invention, the mass fraction of the aluminum oxide dispersion is 5% to 8%.

[0027] According to some embodiments of the invention, the basic compound is ammonia monohydrate.

[0028] According to some embodiments of the present invention, the pH of the reaction is 9-10.

[0029] According to some embodiments of the present invention, the reaction temperature is 20°C to 80°C.

[0030] According to some embodiments of the present invention, the reaction temperature is 40°C to 80°C.

[0031] According to some embodiments of the present invention, the reaction temperature is 60°C to 80°C.

[0032] According to some embodiments of the present invention, the reaction time is 1 h to 10 h.

[0033] According to some embodiments of the present invention, the reaction time is 4 h to 10 h.

[0034] According to some embodiments of the present invention, the reaction time is 4 h to 8 h.

[0035] According to some embodiments of the present invention, the reaction time is 4 h to 6 h.

[0036] According to some embodiments of the present invention, the titanate-modified zirconia includes the following preparation raw materials:

[0037] Titanate and zirconium oxide.

[0038] According to some embodiments of the present invention, D50 of the zirconium oxide is 10 nm to 50 nm.

[0039] According to some embodiments of the present invention, the titanate-modified zirconia comprises the following preparation raw materials in parts by weight:

[0040] 0.3 to 0.4 parts of titanate and 1 part of zirconium oxide.

[0041] According to some embodiments of the present invention, the titanate is butyl titanate.

[0042] According to some embodiments of the present invention, the method for preparing the titanate-modified zirconia comprises the following steps:

[0043] Adding titanate into ethanol to prepare a titanate dispersion;

[0044] Zirconium oxide and bicarbonate solution are added to the titanate dispersion and heated for reaction.

[0045] According to some embodiments of the present invention, the molar concentration of the titanate dispersion is 0.5 mol / L to 0.8 mol / L.

[0046] According to some embodiments of the present invention, the molar concentration of the bicarbonate solution is 0.6 mol / L to 0.8 mol / L.

[0047] According to some embodiments of the invention, the bicarbonate solution comprises at least one of a sodium bicarbonate solution, a potassium bicarbonate solution and an ammonium bicarbonate solution.

[0048] According to some embodiments of the present invention, the temperature of the heating reaction is 50°C to 60°C.

[0049] According to some embodiments of the present invention, the heating reaction time is 6 h to 10 h.

[0050] According to some embodiments of the present invention, the pH of the heating reaction is 7-8.

[0051] According to some embodiments of the present invention, the composite layer further comprises an adhesive and a solvent.

[0052] According to some embodiments of the invention, the binder is carboxymethyl cellulose.

[0053] According to some embodiments of the invention, the solvent is an ethanol aqueous solution.

[0054] According to some embodiments of the present invention, the volume fraction of the ethanol aqueous solution is 50% to 70%.

[0055] According to some embodiments of the present invention, the volume fraction of the ethanol aqueous solution is 50% to 60%.

[0056] According to some embodiments of the present invention, the composite layer is composed of the following raw materials in weight fractions:

[0057] Silicate modified aluminum oxide 50% to 60%, titanate modified zirconium oxide 20% to 30%, chromium oxide 3% to 5%, adhesive 0.2% to 0.5% and the balance is solvent.

[0058] According to some embodiments of the present invention, the composite layer is composed of the following raw materials in weight fractions:

[0059] Silicate modified aluminum oxide 55% to 60%, titanate modified zirconium oxide 20% to 30%, chromium oxide 3% to 5%, adhesive 0.2% to 0.5% and the balance is solvent.

[0060] According to some embodiments of the present invention, the composite layer is composed of the following raw materials in weight fractions:

[0061] Silicate modified aluminum oxide 57% to 60%, titanate modified zirconium oxide 20% to 30%, chromium oxide 3% to 5%, adhesive 0.2% to 0.5% and the balance is solvent.

[0062] According to some embodiments of the present invention, the composite layer is composed of the following raw materials in weight fractions:

[0063] Silicate modified aluminum oxide 57% to 59%, titanate modified zirconium oxide 25% to 30%, chromium oxide 3% to 5%, adhesive 0.2% to 0.5% and the balance is solvent.

[0064] According to some embodiments of the present invention, the composite layer is composed of the following raw materials in weight fractions:

[0065] Silicate modified aluminum oxide 57% to 59%, titanate modified zirconium oxide 27% to 30%, chromium oxide 3% to 5%, adhesive 0.2% to 0.5% and the balance is solvent.

[0066] According to some embodiments of the present invention, the composite layer is composed of the following raw materials in weight fractions:

[0067] Silicate modified aluminum oxide 57% to 59%, titanate modified zirconium oxide 27% to 29%, chromium oxide 3% to 5%, adhesive 0.2% to 0.5% and the balance is solvent.

[0068] According to some embodiments of the present invention, the composite layer has a thickness of 1 mm to 2 mm.

[0069] According to some embodiments of the present invention, the mesh size of the chromium oxide is 300-400 mesh.

[0070] According to some embodiments of the present invention, the ductile iron is composed of the following elements in weight fractions:

[0071] C: 3.4%~3.6%;

[0072] Si: 2.4%~3.0%;

[0073] Mn: 0.4% to 0.5%;

[0074] S: 0.01%~0.03%;

[0075] P: 0.04%~0.06%;

[0076] Mg: 0.03%~0.06%;

[0077] Re: 0.03% to 0.05%; the balance is Fe and unavoidable impurity elements.

[0078] According to some embodiments of the present invention, the method for preparing ductile iron comprises the following preparation steps:

[0079] Ductile iron is made by mixing pig iron and ferromanganese, smelting, spheroidizing and cooling.

[0080] According to some embodiments of the present invention, the smelting temperature is 1480°C to 1500°C.

[0081] According to some embodiments of the present invention, the spheroidizing agent is FeSiMg 8 Re 7 .

[0082] According to some embodiments of the present invention, the spheroidization time is 1 min to 2 min.

[0083] A second aspect of the present invention provides the above-mentioned method of producing ductile iron with a composite layer, comprising the following steps:

[0084] Coating the prepared raw material on the surface of the ductile iron and sintering;

[0085] The sintering temperature is 1100°C to 1200°C.

[0086] According to some embodiments of the present invention, the silicate-modified alumina, the titanate-modified zirconia, the chromium oxide, the binder and the solvent are mixed to prepare a mixed slurry.

[0087] According to some embodiments of the present invention, the mixing is ball milling mixing.

[0088] According to some embodiments of the present invention, the ball milling mixing time is 6 h to 8 h.

[0089] According to some embodiments of the present invention, the ball-to-material ratio of the ball milling mixture is 1:1.5-2.

[0090] According to some embodiments of the present invention, the rotation speed of the ball milling mixing is 100 rpm to 200 rpm.

[0091] According to some embodiments of the present invention, the sintering time is 3 h to 4 h.

[0092] The third aspect of the present invention discloses the use of the ductile iron with a composite layer in the preparation of corrosion-resistant manhole covers. DETAILED DESCRIPTION

[0093] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0094] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0095] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0096] In the embodiment of the present invention, the Re element is lanthanum.

[0097] In the embodiment of the present invention, the aluminum oxide was purchased from VK-L100 of Hangzhou Zhitai Purification Technology Co., Ltd.; α-Al 2 O 3 , particle size is 100nm.

[0098] In the embodiment of the present invention, zirconium oxide is purchased from Jiaozuo Zhongcheng New Materials Co., Ltd., and the average particle size is 10 nm to 20 nm.

[0099] In the embodiment of the present invention, chromium oxide (Cr 2 O 3 ) was purchased from Qinghe County Top Metal Materials Co., Ltd., with a mesh size of 325.

[0100] Example 1

[0101] This embodiment is a ductile iron with a composite layer, wherein the inner layer is ductile iron and the surface of the ductile iron is provided with a composite layer.

[0102] In this embodiment, the ductile iron is composed of the following elements by weight:

[0103] C: 3.5%; Si: 2.5%; Mn: 0.45%; S: 0.012%; P: 0.05%; Mg: 0.03%; Re: 0.04%; the remainder is Fe and unavoidable impurity elements.

[0104] The preparation method of ductile iron in this embodiment comprises the following preparation steps:

[0105] Ductile iron is made by mixing pig iron and ferromanganese, smelting until the solid disappears, spheroidizing, and then cooling to make ductile iron.

[0106] The melting temperature in this embodiment is 1500°C;

[0107] The spheroidizing agent in this embodiment is FeSiMg 8 Re 7 .

[0108] The spheroidization time in this embodiment is 1 min.

[0109] In this embodiment, the composite layer is composed of the following raw materials in weight fraction:

[0110] Silicate-modified alumina 58%, titanate-modified zirconia 28%, chromium oxide 4%, binder 0.5% and the balance being solvent.

[0111] In this embodiment, the silicate-modified alumina is prepared by the following steps:

[0112] Alumina was added into water to prepare an alumina dispersion (mass fraction: 6%);

[0113] Add butyl orthosilicate and ammonia water to the alumina dispersion for reaction (the mass ratio of alumina to butyl orthosilicate is 1:0.15, the reaction temperature is 60°C, the reaction time is 5h, and the reaction pH is 9). After the reaction is completed, separate the solid and liquid, collect the solid phase, and dry it.

[0114] In this embodiment, the titanate-modified zirconium oxide is prepared by the following steps:

[0115] Adding butyl titanate into ethanol to prepare a butyl titanate dispersion (the molar concentration of butyl titanate is 0.6 mol / L);

[0116] Zirconium oxide and ammonium bicarbonate solution (0.6 mol / L) were added to butyl titanate solution for heating reaction (the mass ratio of butyl titanate and zirconium oxide was 0.4:1, the heating temperature was 60°C, the heating time was 8 h, and the reaction pH was 7.5). After the heating reaction was completed, the solid and liquid were separated, and the solid phase was collected and dried.

[0117] The ductile iron with composite layer in this embodiment is composed of the following steps:

[0118] S1. Mixing silicate-modified alumina, titanate-modified zirconium oxide, chromium oxide, a binder (carboxymethyl cellulose) and a solvent (ethanol aqueous solution with a volume fraction of 60%) to prepare a mixed slurry;

[0119] The mixing in this step is ball milling mixing;

[0120] The ball milling time in this step is 8h;

[0121] The ball-to-material ratio of the ball milling mixture in this step is 1:2;

[0122] The speed of ball milling mixing in this step is 200 rpm;

[0123] S2, coating the mixed slurry on the surface of ductile iron, and sequentially drying, sintering and cooling;

[0124] The drying temperature in this step is 100°C;

[0125] The drying time in this step is 6h;

[0126] The heating rate after drying in this step is 10℃ / min;

[0127] The sintering temperature in this step is 1150°C;

[0128] The sintering time in this step is 4 h.

[0129] Example 2

[0130] This embodiment is a ductile iron with a composite layer, which is different from the embodiment 1 in that:

[0131] In this embodiment, the composite layer is composed of the following raw materials in weight fraction:

[0132] Silicate-modified alumina 55%, titanate-modified zirconia 26%, chromium oxide 4%, binder 0.5% and the balance being solvent.

[0133] The preparation method of ductile iron with a composite layer in this step is carried out with reference to Example 1.

[0134] Example 3

[0135] This embodiment is a ductile iron with a composite layer, which is different from the embodiment 1 in that:

[0136] In this embodiment, the composite layer is composed of the following raw materials in weight fraction:

[0137] Silicate-modified alumina 53%, titanate-modified zirconia 22%, chromium oxide 4%, binder 0.5% and the balance being solvent.

[0138] The preparation method of ductile iron with a composite layer in this step is carried out with reference to Example 1.

[0139] Example 4

[0140] This embodiment is a ductile iron with a composite layer, which is different from the embodiment 1 in that:

[0141] In this embodiment, the titanate-modified zirconium oxide is prepared by the following steps:

[0142] Adding butyl titanate into ethanol to prepare a butyl titanate dispersion (the molar concentration of butyl titanate is 0.6 mol / L);

[0143] Zirconium oxide and ammonium bicarbonate solution (0.6 mol / L) were added to butyl titanate solution for heating reaction (the mass ratio of butyl titanate and zirconium oxide was 0.5:1, the heating temperature was 60°C, the heating time was 8 h, and the reaction pH was 7.5). After the heating reaction was completed, the solid and liquid were separated, and the solid phase was collected and dried.

[0144] The preparation method of ductile iron with a composite layer in this step is carried out with reference to Example 1.

[0145] Example 5

[0146] This embodiment is a ductile iron with a composite layer, which is different from the embodiment 1 in that:

[0147] In this embodiment, the silicate-modified alumina is prepared by the following steps:

[0148] Alumina was added into water to prepare an alumina dispersion (mass fraction: 6%);

[0149] Add butyl orthosilicate and ammonia water to the alumina dispersion for reaction (the mass ratio of alumina to butyl orthosilicate is 1:0.3, the reaction temperature is 60°C, the reaction time is 5h, and the reaction pH is 9). After the reaction is completed, separate the solid and liquid, collect the solid phase, and dry it.

[0150] The preparation method of ductile iron with a composite layer in this step is carried out with reference to Example 1.

[0151] Comparative Example 1

[0152] This comparative example is a ductile iron with a composite layer, which differs from Example 1 in that:

[0153] In this comparative example, no chromium oxide was added.

[0154] The preparation method of the ductile iron with a composite layer in this comparative example consists of the following steps:

[0155] S1, mixing silicate-modified alumina, titanate-modified zirconia, a binder (carboxymethyl cellulose) and a solvent (ethanol aqueous solution with a volume fraction of 60%) to prepare a mixed slurry;

[0156] The mixing in this step is ball milling mixing;

[0157] The ball milling mixing time in this step is 8h;

[0158] The ball-to-material ratio of the ball milling mixture in this step is 1:2;

[0159] The speed of ball milling mixing in this step is 200 rpm;

[0160] S2, coating the mixed slurry on the surface of ductile iron, and sequentially drying, sintering and cooling;

[0161] The drying temperature in this step is 100°C;

[0162] The drying time in this step is 6h;

[0163] The heating rate after drying in this step is 10℃ / min;

[0164] The sintering temperature in this step is 1150°C;

[0165] The sintering time in this step is 4 h.

[0166] Comparative Example 2

[0167] This comparative example is a ductile iron with a composite layer, which differs from Example 1 in that:

[0168] In this comparative example, alumina was used to replace silicate-modified alumina.

[0169] The preparation method of the ductile iron with a composite layer in this comparative example consists of the following steps:

[0170] S1. Alumina, titanate-modified zirconium oxide, chromium oxide, a binder (carboxymethyl cellulose) and a solvent (ethanol aqueous solution with a volume fraction of 60%) are mixed to prepare a mixed slurry;

[0171] The mixing in this step is ball milling mixing;

[0172] The ball milling time in this step is 8h;

[0173] The ball-to-material ratio of the ball milling mixture in this step is 1:2;

[0174] The speed of ball milling mixing in this step is 200 rpm;

[0175] S2, coating the mixed slurry on the surface of ductile iron, and sequentially drying, sintering and cooling;

[0176] The drying temperature in this step is 100°C;

[0177] The drying time in this step is 6h;

[0178] The heating rate after drying in this step is 10℃ / min;

[0179] The sintering temperature in this step is 1150°C;

[0180] The sintering time in this step is 4 h.

[0181] Comparative Example 3

[0182] This comparative example is a ductile iron with a composite layer, which differs from Example 1 in that:

[0183] In this comparative example, zirconium oxide is used to replace titanate-modified zirconium oxide.

[0184] The preparation method of the ductile iron with a composite layer in this comparative example consists of the following steps:

[0185] S1. Mixing silicate-modified alumina, zirconium oxide, chromium oxide, a binder (carboxymethyl cellulose) and a solvent (ethanol aqueous solution with a volume fraction of 60%) to prepare a mixed slurry;

[0186] The mixing in this step is ball milling mixing;

[0187] The ball milling time in this step is 8h;

[0188] The ball-to-material ratio of the ball milling mixture in this step is 1:2;

[0189] The speed of ball milling mixing in this step is 200 rpm;

[0190] S2, coating the mixed slurry on the surface of ductile iron, and sequentially drying, sintering and cooling;

[0191] The drying temperature in this step is 100°C;

[0192] The drying time in this step is 6h;

[0193] The heating rate after drying in this step is 10℃ / min;

[0194] The sintering temperature in this step is 1150°C;

[0195] The sintering time in this step is 4 h.

[0196] Comparative Example 4

[0197] This comparative example is a ductile iron with a composite layer, which differs from Example 1 in that:

[0198] In this comparative example, alumina was used to replace silicate-modified alumina;

[0199] Zirconia is used to replace titanate-modified zirconia.

[0200] The preparation method of the ductile iron with a composite layer in this comparative example consists of the following steps:

[0201] S1. Alumina, zirconium oxide, chromium oxide, a binder (carboxymethyl cellulose) and a solvent (ethanol aqueous solution with a volume fraction of 60%) are mixed to prepare a mixed slurry;

[0202] The mixing in this step is ball milling mixing;

[0203] The ball milling time in this step is 8h;

[0204] The ball-to-material ratio of the ball milling mixture in this step is 1:2;

[0205] The speed of ball milling mixing in this step is 200 rpm;

[0206] S2, coating the mixed slurry on the surface of ductile iron, and sequentially drying, sintering and cooling;

[0207] The drying temperature in this step is 100°C;

[0208] The drying time in this step is 6h;

[0209] The heating rate after drying in this step is 10℃ / min;

[0210] The sintering temperature in this step is 1150°C;

[0211] The sintering time in this step is 4 h.

[0212] The corrosion rate test of the ductile iron with a composite layer obtained in Examples 1 to 5 of the present invention and Comparative Examples 1 to 4 was carried out according to the following method:

[0213] The ductile iron with a composite layer prepared in an embodiment of the present invention is made into a sample;

[0214] The sample was immersed in a neutral salt solution (3% NaCl solution by mass) for 12 hours, then taken out and placed in the air for 12 hours; then placed in a neutral salt solution for 12 hours, and then placed in the air for 12 hours, and this cycle was repeated for 30 days (temperature was 25°C); the corrosion rate of the sample was calculated; the test results are shown in Table 1.

[0215] Table 1 Corrosion rate test results of ductile iron with composite layer prepared in Examples 1 to 5 of the present invention and Comparative Examples 1 to 4

[0216] - Corrosion rate Example 1 0.11mm / year Example 2 0.15mm / year Example 3 0.16mm / year Example 4 0.20mm / year Example 5 0.19mm / year Comparative Example 1 0.34mm / year Comparative Example 2 0.39mm / year Comparative Example 3 0.43mm / year Comparative Example 4 0.54mm / year

[0217] In summary, the silicate-modified alumina and titanate-modified zirconia used in the present invention will be converted into oxides after sintering, thereby forming a composite layer composed of mixed oxides; during the sintering process, the oxides will fill each other, thereby improving the density between the composite layers, thereby improving the corrosion resistance of the composite layer; at the same time, chromium oxide can also reduce the sintering temperature, which is beneficial to improving the performance of the composite layer.

[0218] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and the specific implementation of the present invention cannot be limited to these descriptions. For ordinary technicians in the field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.

[0219] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A ductile iron having a composite layer, characterized in that: Including ductile iron, The surface of the ductile iron is provided with a composite layer; The composite layer includes the following raw materials in weight fractions: Silicate modified alumina 50%~60%, titanate modified zirconia 20%~30%, chromium oxide 3%~5%; The raw materials for preparing the composite layer also include an adhesive and a solvent; The adhesive is carboxymethyl cellulose; The solvent is ethanol aqueous solution; The method of providing ductile iron with a composite layer comprises the following steps: Coating the prepared raw material on the surface of the ductile iron and sintering; The sintering temperature is 1100°C to 1200°C; The preparation method of the silicate-modified alumina comprises the following preparation steps: S01, mixing aluminum oxide and water to prepare an aluminum oxide dispersion; S02, adding silicate and alkaline compound to the alumina dispersion to react; The silicate is ethyl orthosilicate; The mass fraction of the aluminum oxide dispersion is 5% to 8%; The alkaline compound is ammonia monohydrate; The pH of the reaction in step S02 is 9-10; The reaction temperature in step S02 is 20°C to 80°C; The preparation method of the titanate-modified zirconium oxide comprises the following steps: S001, adding titanate to ethanol to prepare a titanate dispersion; S002, adding zirconium oxide and bicarbonate solution to the titanate dispersion and heating for reaction; The titanate is butyl titanate; The molar concentration of the titanate dispersion is 0.5 mol / L to 0.8 mol / L; The molar concentration of the bicarbonate solution is 0.6 mol / L to 0.8 mol / L; The bicarbonate solution includes at least one of a sodium bicarbonate solution, a potassium bicarbonate solution and an ammonium bicarbonate solution; The temperature of the heating reaction in step S002 is 50°C to 60°C; The pH of the heating reaction in step S002 is 7-8.

2. The ductile iron with a composite layer according to claim 1, characterized in that: The thickness of the composite layer is 1 mm to 2 mm.

3. The ductile iron with a composite layer according to claim 1, characterized in that: The sintering time is 3h~4h.

4. Use of the ductile iron with a composite layer as claimed in any one of claims 1 to 3 in the preparation of corrosion-resistant manhole covers.